Peace Education as an Orientation for Contemporary Islamic Da'wah - Nazarudin (Ilmina: Journal of Education and Counseling, 2026)
Contemporary social, cultural, and technological developments present new challenges for the practice of Islamic da'wah, particularly in maintaining social harmony and preventing identity-based conflict. This article aims to analyze the concept of peace education as an orientation for contemporary Islamic da'wah in building a culture of peace, tolerance, and social justice. This research employs a qualitative approach with a literature review method drawn from the Quran, Hadith, and literature on da'wah, Islamic education, and peace studies. The results demonstrate that peace education is strongly relevant to fundamental Islamic values ​​such as rahmatan lil 'alamin (mercy for all the worlds), brotherhood (ukhuwah), justice, and deliberation. The integration of peace education principles into Islamic da'wah can be realized through an educative, dialogical, inclusive, and contextual approach, in both formal and informal settings. This approach serves not only as a means of transforming Islamic values ​​but also as a preventative strategy to reduce the potential for conflict and radicalism in society. Thus, peace education becomes a strategic orientation for contemporary Islamic da'wah in creating a peaceful, moderate, and civilized society.